Efficacy, Use, and Acceptability of a Web-Based Self-management Intervention Designed to Maximize Sexual Well-being in Men Living With Prostate Cancer: Single-Arm Experimental Study - Sean R O'Connor; Carrie Flannagan; Kader Parahoo; Mary Steele; Samantha Thompson; Suneil Jain; Michael Kirby; Nuala Brady; Roma Maguire; John Connaghan; Eilis M McCaughan (JMIR Publications, 2021)
BackgroundSexual dysfunction is a frequent side effect associated with different prostate cancer treatment approaches. It can have a substantial impact on men and their partners and is associated with increased psychological morbidity. Despite this, sexual concerns are often not adequately addressed in routine practice. Evidence-based web-based interventions have the potential to provide ongoing information and sexual well-being support throughout all stages of care. ObjectiveThe aim of this study is to examine the efficacy of a web-based self-management intervention designed to maximize sexual well-being in men living with prostate cancer and explore user perspectives on usability and acceptability. MethodsWe used a single-arm study design, and participants were provided with access to the 5-step intervention for a period of 3 months. The intervention content was tailored based on responses to brief screening questions on treatment type, relationship status, and sexual orientation. Efficacy was assessed by using two-tailed, paired sample t tests for comparing the mean differences between pre- and postintervention measurements for exploring the participants' self-reported knowledge and understanding, sexual satisfaction, and comfort in discussing sexual issues. Usability and acceptability were determined based on the program use data and a postintervention survey for exploring perceived usefulness. ResultsA total of 109 participants were recruited for this study. Significant postintervention improvements at follow-up were observed in the total scores (out of 20) from the survey (mean 12.23/20 points, SD 2.46 vs mean 13.62/20, SD 2.31; t88=9.570; P=.001) as well as in individual item scores on the extent to which the participants agreed that they had sufficient information to manage the impact that prostate cancer had on their sex life (mean 2.31/4 points, SD 0.86 vs mean 2.57/4, SD 0.85; t88=3.660; P=.001) and had the potential to have a satisfying sex life following treatment (mean 2.38/4 points, SD 0.79 vs mean 3.17/4, SD 0.78; t88=7.643; P=.001). The median number of intervention sessions was 3 (range 1-11), and intervention sessions had a median duration of 22 minutes (range 8-77). Acceptable usability scores were reported, with the highest result observed for the question on the extent to which the intervention provided relevant information. ConclusionsThis study provides evidence on the efficacy of a tailored web-based intervention for maximizing sexual well-being in men living with prostate cancer. The results indicate that the intervention may improve one's self-perceived knowledge and understanding of how to manage sexual issues and increase self-efficacy or the belief that a satisfactory sex life could be achieved following treatment. The findings will be used to refine the intervention content before testing as part of a larger longitudinal study for examining its effectiveness.